Implementation of Sidoarjo People's Service System (SiPraja) - Ningtias, Mala Nuraif Tri; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the implementation of the Sidoarjo People's Service System (SiPraja) in Boro Village, Tanggulangin District, Sidoarjo Regency, focusing on factors influencing its execution. Using purposive sampling, the research identifies communication, resources, disposition, and bureaucratic structure as key factors affecting policy implementation, in line with George Edward III's framework. Findings reveal that SiPraja has been effectively implemented, with bidirectional communication and sufficient human and infrastructural resources. However, challenges persist in the disposition, particularly in adapting to the SiPraja application, and the absence of a standard operating procedure in Boro Village. This study contributes to the understanding of innovative public service systems, emphasizing the need for addressing disposition challenges for enhanced effectiveness. Highlight : Effective Bidirectional Communication: SiPraja's success is attributed to robust bidirectional communication, fostering interaction between citizens and government officials. Resource Sufficiency: Human resources, facilities, and infrastructure are deemed adequate, contributing to the seamless implementation of SiPraja. Disposition Challenges: Despite overall success, challenges in user disposition towards the SiPraja application highlight the need for targeted interventions and training. Keywords: SiPraja, Public Service Innovation, Policy Implementation, Bureaucratic Reform, Communication